The Role of K 13 in Improving Student Learning Outcomes - Rizka Khoirina Harahap; Hyssa Sihotang; Ruth Natali; Pesta Romauli; Nurmaidah; Laurensia Mesri Perangin Angin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Education is very important for every child in Indonesia. With education, the next generation can develop their abilities to be even better and eliminate illiteracy and numeracy. Education is one means that can improve the quality of children from various aspects of life. Curriculum as a planning, regulatory, monitoring and evaluation tool which is the final process of a curriculum is used as a benchmark for curriculum achievement, the curriculum is also used as a guide in the process of teaching and learning activities so that the learning objectives are to improve student learning outcomes as expected. The curriculum also helps equalize learning materials in all regions of Indonesia. The teacher is one of the spearheads of the successful implementation of the curriculum. Education is a human effort to improve knowledge, ways of thinking, manners, manners, manners, both obtained from formal and informal institutions. To achieve this, proper education is needed. Because one of the goals of education is to determine success in the process of forming the human person itself, of course it is accompanied by the presence of other elements in the educational process.